Low Temperature Calcination of TiO2 and ZnO Particle Film and Evaluation of Their Photocatalytic Activity - Inovasari Islami; Lutfi Naufal Ramadhika; Lusi Safriani; Ayi Bahtiar; Fitrilawati Fitrilawati; Nowo Riveli; Annisa Aprilia (Department of Physics, Sebelas Maret University, 2023)
In this study, TiO2, ZnO, and TiO2/ZnO films were prepared under low calcination temperature and characterized to observe their properties related to photocatalytic performance. The samples were prepared by mixing the gel phase of ZnO precursor, TiO2 anatase powder, triton-x 100, and acetylacetone to produce a paste form for the deposition process. The resulting paste was then deposited by screen printing onto a glass substrate and subjected to calcination at 250C to facilitate the ZnO crystallization and remove other additive materials. XRD analysis confirms that the formation of ZnO and TiO2 crystals was assisted, although their crystallinity was lower than corresponding particulate forms. The lower crystallinity seems to be related by additive materials remains. The surface morphology of each sample was observed by scanning electron microscopy (SEM) imaging, Brunauer–Emmett–Teller (BET), and contact angle examination. Interestingly, both TiO2 and ZnO layers tend to have a hydrophobic surface meanwhile TiO2/ZnO has a hydrophilic surface. BET analysis revealed that ZnO has the highest specific surface area due to a nanosized. FTIR spectra confirmed the presence of appropriate chemical bonds in the ZnO and TiO2 and other additive materials, such as alkyl groups. The photoluminescence (PL) spectrum shows a blue emission associated with intrinsic defects such as vacancies and interstitials of Zn and Ti in all samples. Differences in the photocatalytic performance of film and particulate form for each material were observed and analyzed. All samples' structures, morphology, and PL characteristics were then correlated to their photocatalyst behavior for methylene blue degradation.